Portraits, Facial Perception, and Aspect-Seeing. (3rd January 2022) - Vrahimis, Andreas
Abstract: Is there a substantial difference between a portrait depicting the sitter's face made by an artist and an image captured by a machine able to simulate the neuro-physiology of facial perception? Drawing on the later Wittgenstein, this paper answers this question by reference to the relation between seeing a visual pattern as (i) a series of shapes and colours, and (ii) a face with expressions. In the case of the artist, and not of the machine, the portrait's creative process involves the ability to see both aspects. From the perspective of the image's viewer, the distinction is more difficult to draw. I address this difficulty by further distinguishing between two attributes of portraits: their representational accuracy, and their ability to convey the artist's reflection on her experience of seeing the sitter face-to-face. While artificial intelligence can mimic this latter reflective ability, it cannot exactly reproduce it.